SIKAP RASIONAL GURU MADRASAH ALIYAH (STUDY PADA GURU PAI DI MAN KOTA BANDA ACEH) - Azhari Azhari; Saifuddin Saifuddin; Razali Yunus; Adi Kasman; M Arif Idris (Jurnal Dedikasi Pendidikan, 2024)
Professional teachers are not only required to teach, but must have a rational attitude in all actions in the madrasa. Issues in today's society show that the rationality of teachers must be a concern, especially at the Islamic high school level. In this study wants to reveal how rational the attitude of Islamic religious education teachers with the location of research at the State Islamic high school in Banda Aceh City. The research method used is qualitative. The results showed that;Islamic religious education teachers have applied an attitude of rationality in carrying out their duties and responsibilities, one of which through an attitude of rationality has been able to minimize misunderstandings of students, parents of students towards teachers